Diary, 1901-1969 - Chukovskiĭ, Korneĭ, 1882-1969 (Yale University Press, 2005)
Kornei Chukovsky was the complete man of letters - a literary critic, a writer of verses for children, an authority on children's linguistic creativity and a translator. His diary begins in prerevolutionary Russia and spans almost the entire Soviet era.